Cardiac troponins: Mechanisms of release and role in healthy and diseased subjects. (14th December 2022) - Ragusa, Rosetta; Masotti, Silvia; Musetti, Veronica; Rocchiccioli, Silvia; Prontera, Concetta; Perrone, Marco; Passino, Claudio; Clerico, Aldo; Caselli, Chiara
Abstract: The cardiac troponins (cTns), cardiac troponin C (cTnC), cTnT, and cTnI are key elements of myocardial apparatus, fixed as protein complex on the thin filament of sarcomere and are involved in the regulation of excitation–contraction coupling of cardiomyocytes in the presence of Ca 2+ . Circulating cTnT and cTnI (cTns) increase following cardiac tissue necrosis, and they are consolidated biomarkers of acute myocardial infarction (AMI). However, the use of high sensitivity (hs)‐immunoassay tests for cTnT and cTnI has made it possible to identify a multitude of other clinical conditions associated with increased circulating levels of cTns. cTns can be measured also in the peripheral circulation of healthy subjects or athletes, suggesting that different mechanisms are involved in the release of cTns in the blood independently of cardiac cell necrosis. In this review, the molecular/cellular mechanisms involved in cTns release in blood and the exploitation of cTnI and cTnT as biomarkers of cardiac adverse events, in addition to cardiac necrosis, are discussed.